43. DETERMINATION OF TOTAL FLAVONOIDS IN MULBERRY LEAVES (MORUS ALBA L.) BY VISIBLE SPECTROPHOTOMETRY (Vietnam Journal of Community Medicine, 2025)
Objective: To develop a method for quantifying total flavonoids in Mulberry leaves by visible spectroscopy.Method: To investigate the conditions for sample processing, quantification by visible spectroscopy after coloring with aluminum salt and sodium nitrite in alkaline medium. The amount of total flavonoids in the sample is converted to the equivalent amount of rutin. Validation of the analytical method according to the instructions of AOAC and ICH.Results: 4.00 grams of the sample was ultrasonically extracted for 45 minutes with 100.0 ml of 70% ethanol. Filter and dilute 5 times with distilled water. Take 5.0 ml of the solution into a 25 ml volumetric flask, add 1 ml of 5% sodium nitrite, mix well. Leave for 6 minutes, add 1 ml of 10% aluminum chloride, mix well, leave for 6 minutes. Add 10 ml of 10% sodium hydroxide. Then add distilled water to the mark, mix well and let stand for 15 minutes. The standard solution of rutin 200 µg/ml was carried out in parallel for comparison. The absorbance was measured at 500 nm. The results of the method validation according to the guidelines of AOAC and ICH all met the requirements. The application of the method to test the content of some self-collected samples gave results from 2.87 ± 0.07 to 3.21 ± 0.03 (%).Conclusion: The study has established a simple and reliable method to quantify total flavonoid in Mulberry leaves.
Keywords: Morus alba; flavonoid; visible spectrophotometry.